2008
DOI: 10.1186/1476-4598-7-24
|View full text |Cite
|
Sign up to set email alerts
|

Phenylbutyrate interferes with the Fanconi anemia and BRCA pathway and sensitizes head and neck cancer cells to cisplatin

Abstract: Background: Cisplatin has been widely used to treat head and neck cancer. One of the clinical limitations with this treatment, however, is that tumors that are initially responsive to cisplatin later acquire resistance. We have recently shown that a subset of head and neck cancer cell lines has a defective Fanconi anemia DNA damage response pathway and this defect correlates to cisplatin sensitivity. We have also shown that the histone deacetylase inhibitor phenylbutyrate sensitize human cells to cisplatin. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…As a central link, FANCD2 connects the upstream and downstream portions of the FA pathway, and its suppression will inevitably block the transduction of FA pathway signals (12). Some scholars have found that the downregulation of FANCD2 nuclear foci formation by phenylbutyrate can enhance the sensitivity of HNSCC to cisplatin (13). Other studies have suggested that FANCD2 plays an important role in the maintenance of gene stability and DNA damage repair during radiotherapy (14).…”
Section: Introductionmentioning
confidence: 99%
“…As a central link, FANCD2 connects the upstream and downstream portions of the FA pathway, and its suppression will inevitably block the transduction of FA pathway signals (12). Some scholars have found that the downregulation of FANCD2 nuclear foci formation by phenylbutyrate can enhance the sensitivity of HNSCC to cisplatin (13). Other studies have suggested that FANCD2 plays an important role in the maintenance of gene stability and DNA damage repair during radiotherapy (14).…”
Section: Introductionmentioning
confidence: 99%
“…While similar results of targeting Fanc/Brca pathway in sensitizing chemotherapy were reported in other types of cancers, such as colorectal cancer, peritoneal carcinomas, and multiple myeloma (47)(48)(49)(50), the results from HNSCC are still controversial. It was reported that targeting Fanc/Brca pathway by the histone deacetylase inhibitor phenybutyrate sensitizes human HNSCC cells to cisplatin (51). However, a separate study failed to correlate Fanc/Brca pathway inactivation with cisplatin sensitivity based on lack of evidence of FANCF methylation, and down-regulation of other Fanconi anemia genes (52).…”
Section: Components Of Fa/brca Pathway As Targets For Cancer Therapymentioning
confidence: 97%
“…Therefore, they suggest that the cisplatin-sensitizing effect of phenylbutyrate is related to its role in targeting the expression of the apoptosis-antagonist B-cell lymphoma -extra large (Bcl-XL). [64] Bandres et al, [65] after identifying five microRNAs (miRNAs) downregulated in patients with colorectal cancer (CRC) and located around/on a cytosine-phosphate-guanine (CpG) island, have observed that treatment with a DNA methyltransferase inhibitor (5-aza-2 0 -deoxycytidine) and phenylbutyrate have restored the expression of the three miRNAs hsa-miR-9, hsa-miR-129, and hsa-miR-137 in three CRC cell lines. The expression of hsa-miR-9 is inversely correlated with the methylation of their promoter regions as measured by methylation-specific polymerase chain reaction (PCR) [MSP] and bisulfate sequencing.…”
Section: Phenylbutyrate and Cancermentioning
confidence: 99%
“…The authors conclude that decitabine and the two HDACIs alter AML cell expression of differentiation markers, but the drugs do not have any major influence on cell cycle distribution. [63] Burkitt and Ljungman, [64] after demonstrating that a subset of head and neck cancer cell lines have a defective Fanconi anemia DNA damage response pathway, which correlates with cisplatin sensitivity, have showed that phenylbutyrate sensitizes human cells to cisplatin (cisplatin is a widely used chemotherapeutic agent used against many different types of tumors, but unfortunately tumors initially responsive to it later acquire resistance). The same authors observe that phenylbutyrate (sodium phenylbutyrate 2 mmol/L for 48 hours) sensitizes cisplatin-resistant head and neck cancer cell lines UM-SCC-1, -6, -25 to cisplatin by inhibiting the Fanconi Anemia (FA)/ Breast Cancer (BRCA) pathway through the downregulation of BRCA1 as well as by an FA/BRCAindependent mechanism.…”
Section: Phenylbutyrate and Cancermentioning
confidence: 99%